Knowledge and readiness on waste separation at source among ums foundation students - Sitty Nur Syafa Bakri (Pusat e-pembelajaran, UMS, 2022)
Although various efforts have been made to increase waste recycling rate in Malaysia, the consequences in the number of waste reduction are still nascent. Alternatively, waste separation at source has been introduced, which acquired positive feedback and action from local government and communities. Here, a video-medium was chosen to demonstrate practice in waste separation at source towards foundation students in Universiti Malaysia Sabah (UMS), Malaysia. A questionnaire was constructed to evaluate their knowledge gained and readiness for waste separation. Overall, students answered higher percentages (scale 4-5) for knowledge learned through video visualization. Similarly, students strongly agreed to willingly practice waste separation at source, with 0.76 correlation from the gained knowledge. For immediate action to implement waste separation, 80% chose to adapt Video 1 – Penang versus the Video 2 – Sapporo. However, students have positively responded to the importance of environmental care, thus being motivated for waste separation. This study is essential for future study on a larger scale to eventually decrease the nation’s waste generation and increase recycling rate.